Evaluasi Penetrasi Resin (HNPM/TEGDMA) ke Jaringan Dentin dengan "SEM" - Andi Soufyan; Gunarso Gunadi (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of this study was to evaluate the penetration of 2-Hydroxy-3-(2-napththoxy) propyl methacrylate (HNM) in triethlene glycol dimethocrylate resin into Dentin. The monomer component was a mixtrue of 3.0 wt% HNPM in TEGMA. This was applied to extracted bovine tooth dentin after conditioning with activator of FeCl 3/citric acid in 10 second. SEM examination of the cross-sectioned specimen modified with HCl demineralization showed that a will-developed. Resin honey comb-like structure was create in the dentin surface.